Anomalies in quantum field theories - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction:purpose: Noether’s theorem connects symmetry of the Lagrangian to conserved quantities. Quantum effects cancel the conserved quantities.Methods: Triangle diagram, Path integral, Pauli-Villars regularisation.Results: Quantum effects that spoil conserved quantities of local gauge symmetries endager renormalisability.Conclusion: A careful treatment of anomalies is needed in order to obtain correct results. The π0 → γγ decay is perhaps the most notable “impossible” effect allowed by anomalies.
Keywords: symmetry; quantum anomalies